La guerre baroque : Le héros, le soldat, le paysan - Jean-François Courouau (Lengas)
The Occitan literature reflects the fact that warfare was part of the civilians’ daily lives in the XVIth and XVIIth centuries. It depicts flamboyant heroes of baroque inspiration but gives also a voice to country people exposed to the soldiers’ abuses as well as to the soldiers themselves, that is to say either to the perpetrators or to the victims